The Komiks and Retelling the Lore of the Folk - Reyes, Soledad S (Archīum Ateneo, 2009)
Komiks (comics), which emerged in the 1920s, have captured the Filipinos' imagination, subsequently becoming materials for major motion pictures, yet marginalized in cultural studies. This article offers a diachronic analysis of the komiks between the 1930s and the 1970s to reveal the relationship between selected komiks characters and the folk tradition embodied in epics and legends. It also explains the komiks writers' fascination with the remote past and their construction of heroes and heroines. In illuminating the worldview of writers and readers and the meanings generated when texts and readers interact, this article problematizes the supposition that popular culture is unalloyed escapism.